Naturalistic verbal and non-verbal encouragement in athletic performance assessments: A mixed-methods study - van Meurs, E.; Nieto, M.; Strauss, B.; Harenberg, S. (Journal of Sports Sciences, 2026)
Social influence through verbal encouragement (VE) or non-verbal encouragement (NVE) aims to support athletes by mobilising resources. Its effectiveness has already been studied in sports by comparing performances with or without VE to investigate the performance-enhancing effect. However, these studies use standardised formulations, given at regular intervals by experimenters who are unknown to the participants, reducing the external validity. This may result in an underestimation of the actual effect. To date, no empirical evidence exists to characterise VE and NVE. The present study analyses the quantitative and qualitative characteristics of VE and NVE. We hypothesised that both would become more frequent the more demanding the task becomes. We video-recorded 39 Canadian hockey student-athletes (49% female, Mage = 20.97, SDage = 1.91). VE and NVE of the encouraging athletes on the sideline per second were coded, transcribed, and the content explored using deductive-inductive thematic analysis. We found that VE and NVE increased over time and that male and female athletes encouraged differently. Statements could be classified as informational, appraisal or tangible support. The results of the analysis can be used as a framework for naturalistic encouragement in future operationalisations. Moreover, we highlight the interpersonal differences in encouragement behaviour, specifically between men and women.